Development of machining simulation application using visual basic programming in NX CAM system environment - M. Nafis, O. Z.; Mohamad Hafiz, Mohamad (Centre for Advanced Research on Energy, 2018)
This paper presents the integration of visual basic programming in NX Computer-Aided Manufacturing (CAM) system with 4th axis milling simulations as machining routines. A customized graphical user interface (GUI) was developed to simplify the simulation process planning and reduce the dependency on user’s experience while developing the machining program in NX CAM system. The simulation operation construction code was recorded by using journaling tool that available in NX CAM. Then the code is modified in visual basic program to build custom machining simulation applications. The results indicate that the developed programs are capable to optimize 4th axis machining simulation by reducing the processing steps and time with minimum process planning tasks.